A new genus and species of uncertain phylogenetic position within the family Hydrobiidae (Caenogastropoda: Truncatelloidea) discovered in Tunisian springs - KHALLOUFI, Noureddine; BÉJAOUI, Mustapha; DELICADO, Diana (European Journal of Taxonomy, 2017)
The species richness of the aquatic (non-marine) gastropod family Hydrobiidae Stimpson, 1865 reaches its peak in the European region partly because other areas, such as North Africa, remain to be extensively surveyed. Most of the hydrobiid species described in North Africa have been ascribed to the subfamilies Pseudamnicolinae, Hydrobiinae and the genus Mercuria. Little is known about the presence of other hydrobiid subfamilies. This study examines several specimens of gastropods collected from two springs in Tunisia. Based on a comprehensive literature review and rigorous anatomical and molecular comparisons with known species from North Africa, Europe and Asia Minor of similar morphology, we here describe a new genus, Bullaregia gen. nov., and new species Bullaregia tunisiensis gen. et sp. nov. Although the shell shape of this Tunisian species resembles that of European hydrobiid genera such as Belgrandiella, it differs in other anatomical structures (i.e., penis with a glandular strap-like lobe, and two seminal receptacles, SR1 pedunculate, SR2 sessile and less developed). Using maximum likelihood and Bayesian approaches, phylogenetic relationships inferred from mtCOI sequences point to an independent evolutionary lineage for this new taxon outside Belgrandiella and other known hydrobiid subfamilies.